Análisis de la aplicación de los impuestos verdes, caso: Impuesto a las botellas plásticas no retornables, e impuesto a la contaminación vehicular y sus efectos dentro de la economía en la sociedad, aplicado en el sector norte de la ciudad de Quito. - López Táquez, Jacqueline del Carmen (2013)
In our analysis, we will provide a clearer picture about the procedures, fees, forms, penalties and purposes involved in the application of tax redeemable non-returnable plastic bottles and vehicular pollution tax, just as participation that the society and businesses against these taxes.